Pemeriksaan Viral Nervous Necrosis (VNN) Pada Ikan dengan Metode Polymerase Chain Reaction (PCR) [Viral Nervous Necrosis (VNN) Examination at Fish by Polymerase Chain Reaction (PCR) Method] - Abdul Manan; Elly Fitriatin (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract Fish production annually has increased. Trading activities of Fishery in Indonesia both exports and imports will continue to increase every year. Control and monitoring of fisheries products was transported in Indonesia aims to reduce the risk of entry and spread of pests and diseases of fish in Indonesia. The purpose of Study is to know examination techniques of virus Viral Nervous Necrosis (VNN) at fish by Polymerase Chain Reaction (PCR) method. This Study was held in the Quarantine Fish Quality Control and Safety of Fishery Products (BBKIPM-KHP) Soekarno Hatta Tangerang, Banten on January 12th to February 12th, 2015. The methods of data fetching consisted of primary and secondary data. The data fetching was performed with active participation, observation, interviews, and literature. Examination methods Viral Nervous Necrosis (VNN) by Polymerase Chain Reaction (PCR). Stages of virus examination by PCR method includes necropsy samples, RNA extraction, amplification, electrophoresis, and the diagnosis results using UV transluminator. Fish samples were examined VNN virus consisting of a live fish and frozen fish both commodity exports, imports, or domestic. The results showed that all fish samples are negative infected with the virus VNN.